Implementasi Kurikulum Merdeka Belajar pada Mata Pelajaran PAI dalam Meningkatkan Kreativitas Belajar Siswa di SMKN 1 Kinali Kab. Pasaman Barat - Fatma, Fifi Gustia; J, Jasmienti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research is motivated by the large number of students who are not yet included in the creative criteria, such as: the number of students who are not good at solving problems, the number of students who are less capable in developing talents, the number of students who have difficulty understanding lessons and students must be guided and directed first before being allowed to learn. independently during learning. The research aims to find out how the implementation of the independent learning curriculum can increase student learning creativity and what the impact of implementing the independent learning curriculum at SMKN 1 Kinali, Kab. West Pasaman. The type of research used in this research is descriptive qualitative research and is located at SMKN 1 Kinali, Kab. West Pasaman. The research informants in this study were Islamic Religious Education Teachers as key informants and supporting informants were class X TO 2 students, Curriculum Representatives and School Principals. The data collection techniques used are observation, interviews and documentation. Data analysis uses the Milles and Huberman model, namely data reduction, data presentation, and drawing conclusions/verification. Based on the research results, it can be concluded that the implementation of the independent learning curriculum in Islamic Religious Education at SMKN 1 Kinali has been implemented at the end of the odd semester of the 2022/2023 academic year. The assessment used combines different approaches, starting with face-to-face learning during the post-pandemic era, several learning models were introduced such as project-based learning models, problem-based learning models, discovery learning models, and inquiry learning. The application of differentiated learning as a form of independent curriculum has resulted in a positive transformation in the development of student learning creativity in Islamic Religious Education at SMKN 1 Kinali. The impact of implementing the independent learning curriculum on Islamic Religious Education subjects at SMKN 1 Kinali is that it can increase students' learning creativity, this is proven by the increase in students' abilities after implementing independent learning, increasing critical thinking, emotional sensitivity, being able to develop talents and having strong imagination tall.